Improved access yet inequitable experience: gay, bisexual and other men who have sex with men's views of more inclusive criteria for source plasma donation - Elisabeth Vesnaver; Terrie Butler-Foster; Mindy Goldman; Emily Gibson; Amelia Palumbo; Don Lapierre; Nolan E. Hill; Richard MacDonagh; Kyle A. Rubini; William Bridel; Glenndl Miguel; Andrew Rosser; et al. (BMC, 2023)
Abstract Background Canada has incrementally reduced restrictions to blood and plasma donation that impact men who have sex with men, gay, bisexual, and queer men, and some Two Spirit, transgender and non-binary individuals (MSM/2SGBTQ+). Prior to the launch of a pilot program in 2021 enabling some MSM/2SGBTQ + to donate source plasma, we explored the acceptability of the program among individuals who could become eligible to donate in the program. Methods We invited men identifying as MSM/2SGBTQ + to participate in two consecutive semi-structured interviews to explore their views on blood and plasma donation policy, plasma donation, and the proposed Canadian plasma donation program. Interview transcripts were analyzed thematically and acceptability-related themes were mapped onto the Theoretical Framework of Acceptability. Results Twenty-seven men identifying as having sex with men participated in 53 interviews. Eighteen themes were mapped onto the seven construct domains of the Theoretical Framework of Acceptability. Underlying all aspects of acceptability was a tension between four primary values influencing participants' views: altruism, equity, supply sufficiency, and evidence-based policy. The program was viewed as welcome progress on a discriminatory policy, with many excited to participate, yet tension with inequitable aspects of the program undermined support for the program and interest to contribute to it. The high demands of the program are unique for MSM/2SGBTQ + and are only tolerable as part of a program that is an incremental and instrumental step to more equitable donation policies. Conclusion Findings highlight past experiences of exclusion in Canada as a unique and critical part of the context of the donation experience among MSM/2SGBTQ+. Despite the program's goals of greater inclusivity of MSM/2SGBTQ + individuals, the anticipated experience of the program included continued stigmatization and inequities. Future research should seek to understand the experienced views of MSM/2SGBTQ + donors to ensure that as policies change, policies are implemented equitably.